A dynamic sustainability assessment of algal biorefineries for biofuel production - Culaba, Alvin B. (Animo Repository, 2019)
Algal biofuels negate many of the problems inflicted by other sources of energy on the environment. However, as algal biofuels are diffused into the industry, it is prevented from completely replacing these other energy sources by the negative system feedback resulting from its own growth. These barriers include resource competition with agricultural products, insufficient capacity of biorefineries, and the loss of investor support as new technology and problems bypass it in urgency. The objective of this paper is to develop strategies for the successful of algal biofuels, from a managerial standpoint. The situation was modeled as a feedback system, comprising of loops between the diffusion of algal biofuels and the economic, social, and environmental problems documented in literature. From a sensitivity analysis of the model, two independent policies were found to be capable of overriding the negative feedback from diffusion. In summary, the suggested policies are (1) aggressive investment in anticipation of further growth, and (2) maximizing the additional energy yield contributed by investments from advancements in technology and scaling. © 2019 IEEE.